PENINGKATAN PRESTASI BELAJAR PKn MATERI PROKLAMASI KEMERDEKAAN DAN KONSTITUSI PERTAMA MELALUI METODE THINK-PAIR-SHARE (TPS) DI KELAS VII.B SMP NEGERI 4 SUNGAI AMBAWANG TAHUN PELAJARAN 2018/2019 - Kastono, Kastono (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
This study aims to determine the use of Think Pair Share (TPS) learning methods to improve the achievement of civic education for SMP Negeri 4 Sungai Ambawang Class VII.B students in the 2018/2019 academic year.   This study is a two-cycle classroom action research. Each cycle consists of four phases: planning, action, observation, and consideration. The subjects of this study were SMP Negeri 4 Sungai Ambawang Class VII.B students in 2018/2019, for a total of 27 students. Based on the results of this survey, it has been shown that applying a learning model with the ThinkPairShare learning approach has a positive impact on improving student performance. This is reflected in a more stable understanding of the materials presented by the teacher (the percentage of learning integrity increases from cycles 1 and 2). 64.62%; 78.70%. In Cycle 2, the learning integrity of the classic student was achieved. In particular, in the student survey on the application of the ThinkPairShare (TPS) learning method, researchers did not set specific goals for success and considered the results of the second cycle of the student survey. The statement received a very satisfying answer and was sufficient to explain how enthusiastic the students were about using the Think Pair Share (TPS) learning method.